Ecological and human health implications of mercury contamination in the coastal water - A. Mallongi; A.U. Rauf; R.D.P. Astuti; S. Palutturi; H. Ishak (Global Journal of Environmental Science and Management, 2023)
BACKGROUND AND OBJECTIVES: The increasing population and anthropogenic activities in coastal areas affects the presence of mercury in coastal waters. Therefore, this study aims to 1) assess the ecological and human health risk of mercury contamination in coastal water; 2) analyze the effectiveness of polymer sulfur as an absorbent for mercury.METHODS: A total of fifteen water samples were obtained from the coastal areas of Makassar and were analyzed using cold vapor atomic absorption spectrophotometry. Ecological and human health risks were assessed using established assessment methods by the United States Environmental Protection Agency. The uncertainty and sensitivity tests for independent variables in human health risk were assessed by the Monte Carlo Simulation method. Furthermore, polymer sulfur was used as a promising technique for capturing and reducing the level of mercury in the water column.FINDINGS: The results showed that the mean concentration of mercury was very high and exceeded the values established by the World Health Organization, United States of Environmental Protection Agency, and Indonesian National Standards, indicating elevated risks to the ecosystem and human health in the future. Additionally, the Monte Carlo simulation model revealed that the non-carcinogenic risk caused by mercury exposure in adults and children was greater than 1 (Total Hazard Index>1), indicating the health adverse effects for both receptors. From the simulation results, the concentration of mercury at 23.3% and exposure time of 21.3 percent were the most influential and dominant factors in non-cancer risk for adults and children, respectively. Therefore, mercury concentration needs to be reduced in coastal areas. The application of polymer sulfur is effective for reducing mercury concentration in water with a percentage reduction range of 39 – 100 percent and p-value of 0.001.CONCLUSION: Mercury contamination of coastal water in Makassar city poses ecological and health risks. The application of polymer sulfur is an effective way for reducing mercury in the water column.